(untitled) (Medical Forum Monthly, 2024)
Objective: To study frequency of patterns and manners of asphyxial deaths autopsied at Liaquat University Hospital. Study Design: Retrospective study Place and Duration of Study: This study was conducted at the Department of Forensic Medicine and Office of Police Surgeon- Medico legal section, Liaquat University of Medical and Health Sciences Jamshoro/Hyderabad from January 2010 to December 2014. Materials and Methods: Medicolegal files of autopsy were studied retrospectively. 135 files were finalized after scrutiny of 2033 autopsies. Causes, types and patterns of asphyxia were noted. Essential data was noted in a pre-designed proforma for study purpose. Data variables were analyzed on Microsoft excel and Statistix 8.1 using appropriate statistical tests. P value of ≤0.05 was taken of statistical significance. Results: One hundred and thirty five cases of asphyxial deaths (out of 2033 autopsies) were studied. Age (mean ±SD) was noted as 49.7±8.9 years. Of 135 cases, 65.9% (n=89) were male and 34.07% (n=46) were female (X2 = 112.5 p=0.0001). 28.1% and 8.14% of cases showed ligature and manual strangulation respectively. Hanging, drowning, traumatic asphyxia and throttling were noted in 42.21%, 12.59%, 5.18% and 3.7% respectively. Suicidal deaths in 29.6%, homicidal in 57.03% and accidental asphyxial deaths were observed in 13.33%. Conclusion: Homicidal and suicidal deaths of hanging and strangulation seemed to be the major contributing causes of asphyxial deaths.